Correlation analysis and multilinear regression model for prediction on solid waste generation in Malaysia - Faridah Zulkipli,; Zulkifli Mohd Nopiah,; Noor Ezlin Ahmad Basri,; Cheng, Jack Kie (Penerbit Universiti Kebangsaan Malaysia, 2021)
Increased volumes of solid waste generation continue unabated due mainly to rapid population increase, urban migration, economic enhancements, and modern lifestyles. Two significant factors contributing directly to the higher volumes of solid waste generation are population and gross domestic product (GDP). In Phase 1 of this study, a correlation analysis with a Pearson coefficient of more than 93% (r > 0.93) shows a strong positive linear relationship between the amount of solid waste generation and population and GDP. Phase 2 provides a multilinear regression analysis and the development of a regression model. They indicate that a 1-unit increment in the amount of solid waste generation is caused by 0.06 of the population and 0.119 of GDP while ßo remains constant at 124.449. Therefore, the multilinear regression model in this study can be applied by solid waste management authorities in Malaysia to accurately forecast future solid waste generation volumes. However, further investigation on other significance factors are suggested for future work in order to develop a holistic model for solid waste management in Malaysia.